An additional marker for sperm DNA quality evaluation in spermatozoa of male partners of couples undergoing assisted reproduction technique (IVF/ICSI): Protamine ratio - Amor, Houda; Shelko, Nyaz; Hamad, Mohammed F.; Zeyad, Ali; Hammadeh, Mohamad Eid (Andrologia, 2019)
The aim of this study was to evaluate the relationship between the protamine ratio (P1/P2), DNA fragmentation of spermatozoa and protamine deficiency. Patients were grouped into fertile (G1; n = 151) and sub‐fertile (G2; n = 121). DNA fragmentation in spermatozoa was analysed by a TUNEL assay (terminal deoxynucleotidyl transferase‐mediated deoxyuridine triphosphate nick‐end labelling), and the protamination was determined by CMA3 staining, while Western blot was used to measure protamine P1 and P2. While sperm DNA fragmentation (SDF) and protamine ratio were significantly elevated in G2 compared with G1 (12.31 ± 7.01% vs. 17.5 ± 9.5%; p = .001) and (0.91 ± 0.43 vs. 0.75 ± 0.42; p = .003); respectively, the CMA3 positive showed no difference at all between G1 and G2. In G1, the CMA3 positive correlated negatively with the P1/P2 ratio and SDF (r = −.586, r = −.297; p = .001 respectively). In contrast, the protamine ratio correlated positively with SDF (r = .356; p = .001). In G2, no correlation was observed between CMA3 positive, SDF and the P1/P2 ratio but the P1/P2 ratio showed a positive correlation with SDF (r = .479; p = .001). In conclusion, the spermatozoa DNA deterioration was closely associated with abnormal protamination but showed an association with the protamine ratio, more than with CMA3 positive. Therefore, for the evaluation of DNA damage in spermatozoa, the P1/P2 ratio might act as an additional biomarker.